(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2013)
The Zeolite NaY in pure phase was synthesized from rice husk (RH) following a three step synthetic route. In the preliminary step seed gel was prepared from a mixture of silicate and Na-acetate solution. This step was then followed by the preparation of feedstock gel. The third or final step involved the mixing of seed gel (5%) and feedstock gel (95%) which produced the zeolite of desired phase, NaY. The synthesized zeolite was characterized by FT-IR, XRD, SEM and DLS particle size analyzer and used to treat wastewater containing Cr (VI). The adsorption of Cr(VI) was monitored as a function of pH of the solution, contact time and initial concentration of Cr(VI). The adsorption results revealed that after scaling up the methodology, the synthesized zeolite NaY could be used as a promising cost-effective adsorbent for the treatment of wastewater containing chromium. Bangladesh J. Sci. Ind. Res. 48(2), 81-88, 2013 DOI: http://dx.doi.org/10.3329/bjsir.v48i2.15737